Analisis Hak-hak Dasar Lingkungan Hidup Ajaran Saminisme Dalam Prespektif Konstitusi Republik Indonesia Dan Hukum Islam - Ahmad Ari Fatullah (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2022)
This study aims to determine basic environmental rights based on the teachings of Saminism and regulation of basic environmental rights based on the teachings of Saminism from the perspective of the Constitution of the Republic of Indonesia and Islamic Law. This research method uses normative legal research with statutory, conceptual and Islamic Law approaches. As for the results of the research that the basic rights of the environment based on the teachings of saminism, among others, are 1). The right to be properly cultivated; 2). The right to be planted or planted; 3). The right to be maintained or guarded; 4). Right to be preserved; 5). The right to be used sufficiently, and judging from the arrangement based on the constitution of the Republic of Indonesia, has not been regulated as a basic obligation of Indonesian citizens, but this obligation has been regulated in the PPLH Law, although it has not been clearly and unequivocally related to the form of their obligations as humans or society towards the environment. For this reason, it is necessary to encourage regulation of the basic obligations of Indonesian citizens towards the environment so that there is a balance, environment, sustainability and sustainability both in the constitution of the Republic of Indonesia and the arrangements under it which are strictly related to the form of obligations as humans or society towards the environment.